2021
DOI: 10.3389/fpsyg.2020.601937
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Organizational Requirements for the Ascription of Animal Personality to Social Groups

Abstract: Recently, psychological phenomena have been expanded to new domains, crisscrossing boundaries of organizational levels, with the emergence of areas such as social personality and ecosystem learning. In this contribution, we analyze the ascription of an individual-based concept (personality) to the social level. Although justified boundary crossings can boost new approaches and applications, the indiscriminate misuse of concepts refrains the growth of scientific areas. The concept of social personality is based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 91 publications
(107 reference statements)
0
2
0
Order By: Relevance
“…Despite the recent rise of research that evaluates mechanisms and developmental aspects of foraging behaviours, such as physiology and experience, these findings are ignored by a large gamut of research focusing on ultimate and ecological questions. Other variables have their effect questioned by part of the myrmecologists, like, for instance, the effect of motivational states that could even be associated with some kind of emotion-like subjective state (Baracchi et al, 2017), and the existence of personality in ants (Japyassúet al, 2021). Alternatively, research that evaluates ultimate questions focuses on the evolutionary history and adaptive function; these factors are neglected in some laboratory mechanistic studies.…”
Section: Integrating Tinbergen's Four Approachesmentioning
confidence: 99%
“…Despite the recent rise of research that evaluates mechanisms and developmental aspects of foraging behaviours, such as physiology and experience, these findings are ignored by a large gamut of research focusing on ultimate and ecological questions. Other variables have their effect questioned by part of the myrmecologists, like, for instance, the effect of motivational states that could even be associated with some kind of emotion-like subjective state (Baracchi et al, 2017), and the existence of personality in ants (Japyassúet al, 2021). Alternatively, research that evaluates ultimate questions focuses on the evolutionary history and adaptive function; these factors are neglected in some laboratory mechanistic studies.…”
Section: Integrating Tinbergen's Four Approachesmentioning
confidence: 99%
“…The study of personality is typically linked to the individual level. However, to the extent that cooperative groups differ from one another in their collective behaviours, some authors defend the idea that these groups can also be thought of having collective behavioural types (Japyassú et al, 2021, Pinter-Wollman., 2012. In eusocial insects, for example, some studies assume that, besides individual level, differences in behavioural types can be observed at the species level (e.g.…”
Section: Personality Studies Of Eusocial Invertebratesmentioning
confidence: 99%